حرية التعبير وحماية الحق في السمعة - بوعبدلي, جمال (جامعة الوادي University of Eloued, 2019)
ملخص: تعتبر حرية التعبير عن الرأي من أهم الحقوق السياسية للإنسان التي كرستها المواثيق والدساتير والقوانين في دول العالم المختلفة،سواء تعلق الأمر بحق المواطن في الإعلام أو في حرية الصحافة أو في حق النقد.ولم تعد حرية الصحافة تعني الحق في إصدار الصحف بل صارت تعني أيضا حق المواطن في تعددها والاختيار فيما بينها إلا أن هذا الحق يصطدم بحق آخر ألا وهو الحق في السمعة والذي يعتبر قيدا على حرية التعبير على أساس أن حدود الحق في السمعة تؤثر في مدى الحرية التي تتمتع بها الصحافة تجاه هذا الحق ،على أساس أنه يحق للإنسان أن يحظى باحترام كرامته التي يعتز بها ،وبالتقدير الذي يرى أنه يستحقه من قبل المجتمع في ضوء مكانته الاجتماعية ،فعملية رسم الحدود بين حق التعبير خاصةً بالنسبة للمسائل ذات الطبيعة العامة ،وحق الخصوصية الذى يحمى حق الأفراد فى أن يُتركوا وشأنهم ،وحقهم فى عدم خدش سمعتهم أصبحت ذات أهمية كبيرة خصوصاً مع التطور التكنولوجيا الحاصل في وسائل الإعلام والاتصال . الكلمات المفتاحية: حرية ؛التعبير؛الحق ؛السمعة ؛الشرف ؛الاعتبار Abstract: Freedom of expression is one of the most important political rights of human beings enshrined in the charters, constitutions and laws of the various countries of the world, be it is the right of citizens to the media, freedom of the information or the right to criticize. Freedom of the press is no longer the right to issue newspapers, pluralism it has evolved to incorporate the right to its nevertheless, this often clashes with the right to reputation reputations, which is a restriction on freedom of expression on the grounds that the limits of the right to reputation affect the extent of freedom enjoyed by the press towards this right, on the basism, people are entitled the right to Respect for ther dignity, which car be defined social status. Appreciate from The process of delineating the boundaries between the right to expression, especially for matters common nature, and the right to privacy, which protects the right of individuals to be left alone and their right for their intact reputation, the public space. key words: freedom; expression; right; reputation; honor; consideration
Keywords: حرية ؛التعبير؛الحق ؛السمعة ؛الشرف ؛الاعتبار; freedom; expression; right; reputation; honor; consideration